New Pathophysiological Aspects of Growth and Prevention of Kidney Stones - J. M. Baumann; B. Affolter (Advances in Urology)
Kidney stones probably grow during crystalluria by crystal sedimentation and aggregation (AGN) on stone surfaces. This process has to occur within urinary transit time (UT) through the kidney before crystals are washed out by diuresis. To get more information, we studied by spectrophotometry the formation and AGN of Ca oxalate (Ca Ox) crystals which were directly produced in urine of 30 stone patients and 30 controls by an oxalate (Ox) titration. Some tests were also performed after removing urinary macromolecules (UMs) by ultrafiltration. To induce rapid crystallization, high Ox additions (0.5–0.8 mM) were necessary. The most important finding was retardation of crystal AGN by UM. In urine of 63% of controls but only 33% of patients, no AGN was observed during an observation of 60 minutes (P<0.05). Also growth and sedimentation rate of crystals were significantly reduced by UM. For stone metaphylaxis, especially for posttreatment residuals, avoiding dietary Ox excesses to prevent crystal formation in the kidney and increasing diuresis to wash out crystals before they aggregate are recommended.